INVESTIGATE THE DETERMINANTS OF TAIWAN FIRMS ENGAGE IN OFDI - Feng Jin-Wei; Cheng Yu-Jen (PEOPLE: International Journal of Social Sciences, 2025)
In recent years, the trend of Taiwan’s OFDI flows shows growing. How to identify the critical factors for local firms to engage in OFDI successfully and rank their priority becomes an important issue. This article employs the DANP method to explore the criteria and their priority of Taiwan’s MNEs engaging in OFDI. The fourteen evaluation criteria are firstly extracted from past literature and are categorized into four groups; then consult with ten scholars/experts who are excellent in international trade; finally, interview with another fourteen senior managers to collect their practical opinions. The research results reveal that The Operation Environment group is the “main cause-factor” while Market Seeking group is the “main effect-factor” among the clusters. Resource Seeking group has the significant relationship with other clusters and locates at the central role among the four groups. This article also distinguishes the industry into two groups: high tech industry and traditional industry. For high tech industry, the top three important criteria are Geopolitical, Industrial Cluster, and Operating Costs; the last three criteria are Market Size, Market Potential, and Partnership. While the top three important criteria for traditional industry are Operating Cost, Labor Availability, and Market Size; the last three criteria are Home Government Polices, Market Potential, and Industrial Cluster. This article also finds that Taiwan’s high-tech industries should emphasize global deployment to mitigate the impact on parent companies when the business environment in host countries deteriorates. On the other hand, Taiwan’s traditional industries should pursue larger markets and lower production costs, as economies of scale are the primary source of their competitive advantage.